2006
DOI: 10.3184/030823406777410990
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of substituted 1,2,4-triazoles

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This methodology was widely used in our group for the synthesis of a new series of optically active ghrelin receptor ligands, starting from various hydrazides and thioamides. [49][50][51][52] Wu et al 53 demonstrated that this method is applicable to microwave technology, but they only used unasymmetric precursors. Apart from the fact that the reaction time is significantly reduced, there was no other significant improvement in the reaction by using microwave technology.…”
Section: Thioamide Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology was widely used in our group for the synthesis of a new series of optically active ghrelin receptor ligands, starting from various hydrazides and thioamides. [49][50][51][52] Wu et al 53 demonstrated that this method is applicable to microwave technology, but they only used unasymmetric precursors. Apart from the fact that the reaction time is significantly reduced, there was no other significant improvement in the reaction by using microwave technology.…”
Section: Thioamide Precursorsmentioning
confidence: 99%
“…To our knowledge, this method is the only one evidencing the possibility to introduce a chiral carbon atom in α of the position 3 of a 3,4,5-trisubstituted 1,2,4-triazole ring, keeping the optical purity of the chiral center. This methodology was widely used in our group for the synthesis of a new series of optically active ghrelin receptor ligands, starting from various hydrazides and thioamides. Wu et al demonstrated that this method is applicable to microwave technology, but they only used unasymmetric precursors. Apart from the fact that the reaction time is significantly reduced, there was no other significant improvement in the reaction by using microwave technology.…”
Section: Synthesis Via N-acylamidrazone Intermediatesmentioning
confidence: 99%
“…S-Ethyl thioamides 186 react with acyl hydrazides 187 in refluxing n-butanol to give 3,4,5-trisubstituted 4H-1,2,4-triazoles 188 (Scheme 12.62) [235]. An efficient synthesis of substituted 1,2,4-triazoles involved condensation of benzoyl hydrazides with thioamides under microwave irradiation [236] cyclize, and release preparation of 3-thioalkyl-1,2,4-triazoles mediated by the polymer-bound base P-BEMP has been described [240].…”
Section: Reactions Of Hydrazonesmentioning
confidence: 99%